AKAD NIKAH VIA INTERNET (Mazahib, 2013)
The phenomenon of marriage via the Internet is a matter that should be reviewed and commented upon by the experts of Islamic family law in Indonesia. Practice ceremony remotely using this technology media has never even met the previous era. Practice ceremony at the time of the Prophet and the righteous Salaf simply implies permissibility tawkil method, ie, if the contract understudy contract actors (both guardian and groom) was unable to do so. Problems in marriage are done via the internet. On the use of internet facility (on-line), we can see the other person exactly like the original and the same words spoken by what diucaapkannya according to the time when he was talking. This certainly will not reduce the validity of a marriage contract terms as described above, for granted consent and can be done with a clear and done at one time and future wife, guardians and witnesses could see the presence of the husband candidates via the Internet (on-line). There is a difference of opinion in the use of the word sahnnya assemblies on a contract requirement. Jumhurul scholars interpret the word "assembly" is the "time and circumstances or continuous". While some scholars argue that the word "assembly" that means "place", For some scholars, the contract may be performed at different times and places only on probate issues.